2021
DOI: 10.3233/jad-210333
|View full text |Cite
|
Sign up to set email alerts
|

Influence of White Matter Hyperintensities on Baseline and Longitudinal Amyloid-β in Cognitively Normal Individuals

Abstract: Background: The associations between small vessel disease (SVD) and cerebrospinal amyloid-β1-42 (Aβ1-42) pathology have not been well-elucidated. Objective: Baseline (BL) white matter hyperintensities (WMH) were examined for associations with month-24 (M24) and longitudinal Aβ1-42 change in cognitively normal (CN) subjects. The interaction of WMH and Aβ1-42 on memory and executive function were also examined. Methods: This study included 72 subjects from the Alzheimer’s Disease Neuroimaging Initiative. Multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…Additional support for this less prominent pathway comes from a study of CU participants 243 in which lower baseline CSF Aβ42 together with higher WMH were associated with worse memory but not executive function. Small vessel disease early in AD progression combined with abnormal Aβ may therefore promote an AD-typical disease pathway characterized by memory impairment.…”
Section: Contribution Of Cerebrovascular Disease To Disease Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional support for this less prominent pathway comes from a study of CU participants 243 in which lower baseline CSF Aβ42 together with higher WMH were associated with worse memory but not executive function. Small vessel disease early in AD progression combined with abnormal Aβ may therefore promote an AD-typical disease pathway characterized by memory impairment.…”
Section: Contribution Of Cerebrovascular Disease To Disease Progressionmentioning
confidence: 99%
“…The authors suggested that this latter Aβ‐mediated pathway reflects exacerbation of AD‐related pathology via reduced Aβ clearance and/or induction of neuroinflammatory responses, as described in Sections 3.2.2 and 3.2.3 . Additional support for this less prominent pathway comes from a study of CU participants 243 in which lower baseline CSF Aβ42 together with higher WMH were associated with worse memory but not executive function. Small vessel disease early in AD progression combined with abnormal Aβ may therefore promote an AD‐typical disease pathway characterized by memory impairment.…”
Section: Adni's Contributions To Understanding Ad Disease Progressionmentioning
confidence: 99%
“…In observational studies, increases in WMH are associated with both cumulative and longitudinal Aβ burden, even in healthy controls 5 . In contrast, WMH presence is less associated with cerebrospinal fluid t‐tau or p‐tau.…”
Section: Introductionmentioning
confidence: 95%
“…4 In observational studies, increases in WMH are associated with both cumulative and longitudinal Aβ burden, even in healthy controls. 5 In contrast, WMH presence is less associated with cerebrospinal fluid t-tau or p-tau. In the ATN framework, amyloid accumulation occurs earlier in the disease suggesting that WMH changes might occur earlier in the AD process.…”
Section: Introductionmentioning
confidence: 97%
“…In a survey conducted by 16 dementia specialists from nine Asia Pacific countries, the co-existence of AD and CVD accounted for 10–20% of all dementia cases in Asia [ 5 ]. This high burden of AD and CVD in the Asian dementia population can also further accelerate underlying amyloid and tau pathology, contributing to poor cognitive outcomes [ 6 ]. The apolipoprotein E ( APOE ) ɛ4 allele is the most common genetic variant associated with AD, and its frequency is seemingly dependent on racial and regional differences.…”
Section: Introductionmentioning
confidence: 99%